Protective Effect of Curcumin on CA1 Region of Hippocampus in Rat Model of Ischemia/Reperfusion Injury: - Yavari, Negin; Sharifi, Zahra Nadia; Rekabdar, Yasamin; Movassaghi, Shabnam (Galen Medical Journal, 2022)
Background: The brain is the most complex and vital organ of the human body. It requires 20-25 % of the total oxygen supply. Because of the limited oxygen and glucose reserves, brain tissue is sensitive to ischemic injury. Indeed, the tolerance of brain tissue for ischemic injury is fragile. Currently, few therapeutic strategies could provide complete neuroprotection. Despite decades of intense research, the beneficial treatment of stroke remains limited. Hence, we aimed to investigate the effect of curcumin on the CA1 region of the hippocampus in a rat model of ischemia/reperfusion (I/R) injury. Materials and Methods: In this experimental research, 24 male Wistar rats were randomly divided into three groups (n=8 per group) as control, I/R, and I/R plus curcumin. All rats underwent bilateral common carotid artery ligation followed by reperfusion. In the treatment group, curcumin (300 mg/kg) was injected 30 minutes before ischemia. Morphological changes of the hippocampus were assessed using Nissl staining, and apoptosis was determined via TUNEL immunohistochemical assays. Results: Nissl staining data showed that the administration of curcumin significantly ameliorated the CA1 pyramidal cell loss due to transient global I/R injury. TUNEL immunohistochemical assays demonstrated that the number of apoptotic cells was significantly lower in the curcumin group than in the I/R groups. Conclusion: Our study demonstrates that curcumin had beneficial activity against ischemia and played a neuroprotective role in the pathogenesis of I/R injury.